The Relationship between Income Inequality, Economic Growth, Inflation, and Unemployment in West Java Province - Muhammad Fauzan; Fisy Amalia; Helmi Ali (Westscience Press, 2023)
This study uses panel data analysis and regression analysis to examine the relationship between income inequality, economic growth, inflation, and unemployment in West Java Province. The results of the panel data analysis indicate that income inequality, inflation, and unemployment significantly negatively affect economic growth. The regression analysis shows that income inequality significantly affects unemployment, while economic growth and inflation have a significant positive effect on unemployment. The study suggests that income inequality, inflation, and unemployment are important factors that affect economic growth and unemployment rates in West Java Province.